The mystery of the stolen statue - Stanley, George E.; Murdocca, Sal. (New York : Aladdib Paperbacks, 2004)
The Third-Grade Detectives are looking forward to their field trip to a local art museum, where a priceless fifteenth-century statue of Joan of Arc is on loan from a Paris museum. But they discover the statue has been stolen. The police find the statue smashed and thrown in a Dumpster. It looks like a case for the Third Grade Detectives even if the museum director doesn't want their help.
6-9.
Accelerated Reader AR
Keywords: Mystery and detective stories